SDGs and Class Teacher Strategies: Efforts to Form Students Coliteness Ethics - Fatma Nurmulia; Ummah Karimah; Sarah Fitrianti; Oriza Alisya Putri (EDUKASI, 2025)
This research is motivated by the fact that there are still many students who have low politeness ethics, so this can be overcome through the classroom teacher's strategy in shaping politeness ethics education. Politeness ethics education is an effort to educate children to make wise decisions and practice them in everyday life. The purpose of this research is to find out the classroom teacher's strategy in shaping the ethics of courtesy of madrasah ibtidaiyah students in facing sustainability in education. The method used is a qualitative method with a case study approach through interviews with grade 3 teachers, grade 3 students, parents of grade 3 students, and interview documentation about the formation of students' independent personal character. The results of the research obtained are that the classroom teacher's strategy in shaping politeness ethics at school for third-grade students of Madrasah Ibtidaiyah Al-I'Tishaam Pondok Cabe South Tangerang is by getting students used to doing habits that can form independent personal character, such as morning dhikr, saying greetings when entering class, salim to teachers, and speaking kindly and politely to teachers and peers.